Dietrich Bonhoeffer's letters and papers from prison : a biography - Marty, Martin E., 1928- (Lives of great religious books., 2011)
Martin Marty tells how and why Letters and Papers from Prison has been read and used in such dramatically different ways, from the cold war to today. --from publisher description.